Information Frictions, Investment Promotion, and Multinational Production: Firm-Level Evidence - Jerónimo Carballo; Ignacio Marra de Arti\~nano; Christian Volpe Martincus (Center for Economic Studies and Ifo Institute (CESifo), 2021)
While countries make use of a wide range of policies to attract multinational firms, identifying the effect of such policies is difficult. Combining firm-level data on both the location of these firms' foreign affiliates and detailed service-specific information from Costa Rica's investment promotion agency (IPA) over time, we find that IPA support significantly increases the probability that a multinational firm establishes its first affiliate in the country, but has generally no impact on the expansion of its presence thereafter. We then show that this effect is primarily driven by the resolution of information asymmetries. It is stronger for IPA information services and on multinational firms from countries and in sectors facing more severe information frictions.
Keywords: F23; F13; F14; L23; L25; L52; O25; 330; information frictions; investment promotion; multinational production